Variations of dry eye disease prevalence by age, sex and geographic characteristics in China: a systematic review and meta-analysis - Song, Peige (J Glob Health, 2018)
BACKGROUND: Dry eye disease (DED) is one of the most prevalent ocular diseases in the world. In China, new lifestyles driven by information technology and the rapid ageing process have brought DED a severe public health concern. The aim of our study was to obtain the pooled prevalence of DED in China and explore its potential correlates. METHODS: A comprehensive systematic review was conducted to identify all relevant literature published since 1990. Meta-analysis and meta-regression approaches were adopted to estimate the prevalence of DED. The number of people with DED was obtained by multiplying the corresponding demographic data in 2010. RESULTS: Advanced age, female sex and larger latitude were significant risk factors for DED by symptoms and signs, whereas only advanced age was positively associated with an increased prevalence of DED by symptoms. In 2010, the prevalence of DED by symptoms and signs were 13.55% (95% CI = 10.00-18.05) and that of DED by symptoms was 31.40% (95% CI = 23.02-41.13) in Chinese people aged 5-89 years, corresponding to a total of 170.09 million (95% CI = 125.52-226.63) and 394.13 million (95% CI = 288.99-516.30) affected individuals respectively. CONCLUSIONS: The huge burden of DED in China calls for more public health attention and actions. Improved epidemiological studies on DED prevalence are still urgently needed.